Nutrition in HNSCC: is it a matter for oncologists? The role of multidisciplinary team—a narrative literature review - Denaro, Nerina; Bareggi, Claudia; Galassi, Barbara; Beltramini, Giada; Wekking, Demi; Proh, Michele; Ibba, Tullio; Solinas, Cinzia; Garrone, Ornella (Frontiers in Oncology, 2024)
Background Malnutrition, defined as weight loss and unsatisfactory nutrient intake, is very common in patients with head and neck squamous cell carcinoma (HNSCC) in either the early or palliative setting. Despite increased awareness, nutritional programs are not yet adequately implemented in these patients. There are several reasons for this delay: differences in composition, the expertise of the multidisciplinary teams involved in HNSCC patients’ treatment, and economic and network resources conditioning faster or slower nutritional supply delivery. This situation affects the outcomes and the quality of life of HNSCC patients. Materials and methods We investigated available literature about nutritional support in HNSCC patients and its impact on outcomes, prognosis, and quality of life, and we focused on the role of the multidisciplinary team. We considered 8,491 articles, and after excluding duplicates and manuscripts not written in English, 1,055 were analyzed and 73 were deemed eligible for the present work. Results After the literature review, we can state that malnutrition, sarcopenia, and cachexia are associated with systemic inflammation and closely correlated with poor outcomes. An evaluation of the nutritional status of the multidisciplinary team before, during, and after therapy could improve patient outcomes, as the goal of the therapeutic approach is widely designed. Conclusions We suggest that the treatment workflow definition is fundamental and propose a tailored nutritional approach that could benefit HNSCC patients’ outcomes and quality of life. These results could be achieved by a multidisciplinary team.